Pengaruh Metode Proyek dan Metode Bercerita Terhadap Karakter Peduli Lingkungan Anak Usia Dini - Laila, Nurlaila Chairunissa; Shofa, Mila Faila (Universitas Muhammadiyah Surakarta, 2025)
This research is motivated by the low character of children's environmental care. This can be seen from many children who throw garbage out of place, have not been able to sort garbage according to its type, and there are still children who like to pull flowers and leaves on plants in the school environment, there are still many children who do not keep their class clean. This study aims to determine the difference in the development of children's environmental care character between those treated with the project method and the storytelling method at Al Anis Islamic Kindergarten. The research method used was experimental method with posttest only design. The research data were obtained using performance tests. The analysis techniques used were unit analysis, prerequisite test, and hypothesis testing. The results of the study obtained a t value of 3,92 and a t table value at a significant level of 5% of 3,044, so that t count > t table is 3,92 > 3,044. These results indicate that there is a difference in the development of children's environmental care character between those treated with the project method and the storytelling method at Al-Anis Islamic Kindergarten.